Intrument for Evaluating Didactical Performance of Clinical Skill Laboratory Teachers - Ide Pustaka Setiawan; Jan Van Dalen Jan Van Dalen; Jill Whittingham Jill Whittingham (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: There are some studies about strategies for clinical skills teachers and criteria for effective teaching in a Skills lab. However, there isn’t an established instrument yet to evaluate clinical skills teacher’s didactical performance while facilitating skills learning. The aim of this study was to develop an appropriate instrument to evaluate clinical skills teachers’ didactical performance.Method: A preliminary instrument was developed based on recent available literatures. This instrument was applied by students, to quantitatively evaluate didactical performance of skills teachers who teach a certain skill. Then focus group discussions (FGD) were conducted. The results of both procedures were compared.Results: 255 first year medical students participated (response rate: 91%). There was significant difference between students’ judgments of clinical teacher’s (specialist) and Skills lab teacher’s (general practitioner) didactical performance (p<0.05). Cronbach’s alpha of the instrument turned out to be .95, indicating a high homogeneity. All items contributed to this measure of reliability. This quantitative finding was supported by qualitative resultsConclusion: The questionnaire developed is valid and reliable. It can be concluded that characteristics of a proper instrument for evaluating clinical skills teachers’ didactical performance encompass didactic skill, interpersonal & communication skills and condition/strategy of skills training.